Leishmaniasis in cat shelters: A serological, molecular and entomological study - Leonel, João Augusto Franco; Vioti, Geovanna; Alves, Maria Luana; Benassi, Julia Cristina; Silva, Diogo Tiago da; Spada, Julio Cesar Pereira; Ruiz, Vera Letticie de Azevedo; Starke-Buzetti, Wilma Aparecida [UNESP]; Soares, Rodrigo Martins; Oliveira, Trícia Maria Ferreira de Sousa (Hindawi, 2020)
An epidemiological Leishmania spp. and entomological Phlebotomine sandflies survey was performed in cat shelters at leishmaniasis endemic area of Brazil. Blood and conjunctival swab (CS) samples were collected from 94 cats in two animal protection shelters. These samples were subjected to serological tests using the indirect immunofluorescence antibody test (IFAT) and indirect enzyme-linked immunosorbent assay (ELISA) and to molecular test by polymerase chain reaction (PCR). In addition, a Phlebotomine sandflies survey was performed in the same shelters. The analyses revealed a positivity of 31.91% (30/94) through ELISA and 29.79% (28/94) through IFAT. The two serological tests showed a positive association with perfect agreement (k = 0.925). None of the cats were positive by Leishmania spp. DNA. One Lutzomyia (Lutzomyia) longipalpis male was found in one of the cat shelters. The results and the implications of our findings are discussed below.
Keywords: Felis catus; Leishmania spp.; Lutzomyia longipalpis; PCR; serology